A destructible headform for the assessment of sports impacts. (March 2023) - Stone, Ben; Mitchell, Sean; Miyazaki, Yusuke; Peirce, Nicholas; Harland, Andy
Commercially available headforms, such as the Hybrid-III and EN 960 headforms, have been used effectively to investigate the mechanics of head impacts. These headforms may result in accelerations that are unrepresentative of a human head in some impact scenarios. This may be important when considering impacts that produce areas of high pressure, since skull deformation and resonance excitation may influence the dynamic response. The National Operating Committee on Standards for Athletic Equipment (NOCSAE) headform may produce a more suitable response during these types of impacts due to the more representative skull component. However, permanent deformation may occur in some unprotected impact scenarios, resulting in the entire headform needing to be replaced. This paper outlines the development of a novel, modular and destructible headform (LU headform) that can be used in potentially destructive testing, where individual components can be replaced. The LU headform was modelled after a UK 50th percentile male. The inertial properties of the LU headform were within 6% of those observed in humans. The skull simulant properties were within the range of values reported for human tissue in two build orientations, but lower in one build orientation. The lowest and highest resonance frequencies observed in the headform model were within 5% of those observed in humans. Drop and projectile tests were conducted in line with previous cadaver tests with the observed accelerations within the range reported for post-mortem human subjects. The LU headform offers a practical means of simulating head dynamics during localised unprotected impacts or in protected impacts where local deformation and/or resonance frequency excitation remains possible.